Development and implementation of a wearable system with ear-EEG for the monitoring of epileptic seizures (2020)
The diagnosis of Epileptic seizures is made by electroencephalograph equipment in a clinical environment. The problems of these equipment are the short recording time (20 to 30 minutes) and the different conditions between a clinical environment and an external environment. This paper presents a solution of these problems with the development of a wearable system with ear-EEG for the monitoring of epileptic seizures, that allows a longer time for continue monitoring of EEG signals and the tests can realize in an ambulatory environment